Kvinners og menns fortellinger om den russisk-norske grensen - Olsen, Kjell (Tidsskrift for kulturforskning, 2011)
This article discusses the gendered way of plotting narrations about the Russian-Norwegian border. Analysis of narratives is understood as a way to reveal the expression of important values in local communities as well as a way to understand how the narrator situates him- or herself in time and space in an ever-changing cultural and social context. What this analysis reveals is that men's narrations tend to be organised by plots that goes from a macro context to a micro context, in contrast to women's narrations. This gendered difference is explained by the social construction of the border that situates women and men differently and the immediate context of narration.